2020
DOI: 10.7150/jca.39884
|View full text |Cite
|
Sign up to set email alerts
|

MiR-195-5p is a Potential Factor Responsible for CPNE1 Differential Expression between Subtypes of Non-Small Cell Lung Cancer

Abstract: Purpose: Lung cancer is the most common malignancy with poor 5-year survival among men and women. Previous studies have shown that CPNE1 is up-regulated in non-small cell lung cancer (NSCLC). However, whether and how CPNE1 expression varies between different subtypes of NSCLC remains less understood. Methods: Bioinformatical analysis and GSE19188 were selected to confirm CPNE1 expression in different subtypes of NSCLC. Four microRNA prediction websites and GSE53883, GSE43000 were used to evaluate the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…All procedures were performed as previously described 21 . The following primers were used for qRT-PCR: for HIF-1α, 5′-ATCCATCTGACCATGAGGAAATG-3′ (forward) and 5′-TCGGCTAGTTAGGGTACACTTC-3′ (reverse); and for NRP1, 5′-GAAAAATGCGAAT…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were performed as previously described 21 . The following primers were used for qRT-PCR: for HIF-1α, 5′-ATCCATCTGACCATGAGGAAATG-3′ (forward) and 5′-TCGGCTAGTTAGGGTACACTTC-3′ (reverse); and for NRP1, 5′-GAAAAATGCGAAT…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs are small non-coding RNAs, 18-22 nucleotides in length, that serve important functions in cell physiology by regulating the expression of mRNAs (16). An increasing amount of evidence has suggested that miR-195-5p functions as a tumor suppressor in numerous types of cancer, including non-small cell lung (NSCLC), cervical and prostate cancers (17)(18)(19)(20)(21)(22)(23)(24). For example, in NSCLC, miR-195-5p overexpression inhibited cell proliferation and induced apoptosis by directly targeting CIAPIN1 (17) and CEP55 (18), and inhibited cell proliferation, migration, and…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiles and clinical information for OC were downloaded from TCGA using the UCSC Xena Browser 3 ( Pu et al, 2019 ; Du et al, 2020 ; Zhang Z. et al, 2020 ), and TCGA ovarian carcinoma gene expression data were obtained using the AffyU133a array. Scores were computed with the ESTIMATE algorithm 4 .…”
Section: Methodsmentioning
confidence: 99%